Իրավական պետություն և իրավագիտակցություն - Ս. Մ. Բարսեղյան (ՀՀ ԳԱԱ հրատ.)
Изменение ситуации в современном мире, вызванное глобализацией, перед исследователями правовой сферы выдвигает вопросы, имеющие отношение как к теории правового государства и гражданского общества, так и к характеру их взаимодействия и взаимообусловленности. The change in the situation in the modern world, caused by globalization, raises questions before the researcher in the legal sphere, concerning the theory of the rule of law and civil society, as well as the nature of their interaction and interdependence.
Keywords: Law